2020
DOI: 10.1007/s00405-020-05798-y
|View full text |Cite
|
Sign up to set email alerts
|

Psychological distress and nutritional status in head and neck cancer patients: a pilot study

Abstract: Purpose To determine whether the psychological state of patients with head and neck cancer (HCN) is associated with their nutritional status. Methods In 40 patients with locally advanced HNC treated with definitive or adjuvant (chemo)radiotherapy, psychological and nutritional status were assessed before treatment, at its completion and 3 months' post-therapy. Psychosocial distress was measured using the Hospital Anxiety and Depression Scale questionnaire (HADS-A, HADS-D), whereas the nutritional status was ev… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
1

Year Published

2020
2020
2022
2022

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 20 publications
(20 citation statements)
references
References 32 publications
0
14
1
Order By: Relevance
“…We found an association between presenting anxious and depression symptomatology and malnutrition in hospitalized oncologic patients. Previous studies also point towards this association [27][28][29][30][31][32]. Chabowski et al found that the deterioration in nutritional status is associated with a signi cant worsening in terms of depression, anxiety, and pain.…”
Section: Discussionmentioning
confidence: 90%
See 1 more Smart Citation
“…We found an association between presenting anxious and depression symptomatology and malnutrition in hospitalized oncologic patients. Previous studies also point towards this association [27][28][29][30][31][32]. Chabowski et al found that the deterioration in nutritional status is associated with a signi cant worsening in terms of depression, anxiety, and pain.…”
Section: Discussionmentioning
confidence: 90%
“…[28]. Gosak et al found a signi cant correlation between nutritional status and HADS scores, with more distressed patients found in the malnourished/cachectic subgroups [29]. Santos et al found the presence of depression in 52.9% elderly malnourished patients undergoing treatment for cancer [33].…”
Section: Discussionmentioning
confidence: 99%
“…Variability in rates of depression were noted and ranged from 2% to 84% due to differential timing of assessments, different scales, and different threshold values. For example, across different studies, depression was evaluated using any of the following instruments: Hospital Anxiety and Depression Scale (HADS) [16][17][18][19][20][21][22][23][24][25]35,36], the Beck Depression Inventory (BDI) [26][27][28], the short-form of the Geriatric Depression Scale (GDS-SF) [29], the Neuropsychiatric Inventory Questionnaire (NPI-Q) [30], the Research Diagnostic Criteria Schedule for Affective Disorders and Schizophrenia (RDC SADS) [31], the University of Washington Quality of Life Mood scale (UWQOL-mood) [32], and the Patient Health Questionaire-8 (PHQ-8) [4]. Chen et al [16] evaluated the prevalence of depression over time using the HADS-D (cut-off score of ≥8) and the BDI (cut-off score ≥ 14) and reported a 13% difference in the number of patients with depression as identified by the HADS-D and the BDI at pre-treatment, a 5% difference in prevalence during treatment, and a 12% difference post-treatment between instruments.…”
Section: Depressionmentioning
confidence: 99%
“…Twenty studies reported on prevalence of anxiety in HNC [4,[16][17][18][19][20][21][22][23]25,30,33,[35][36][37][42][43][44][45][46]. Sample sizes ranged from 23 patients to 229 patients and prevalence rates ranged from 1% to 97.5%.…”
Section: Anxietymentioning
confidence: 99%
“…Malnutrition in patients with HNC is linked with signs of psychological distress, and includes adjusting to physical changes that may impact body image, such as rapid weight loss, or the impact of changes to the social meaning of eating [ 84 ]. Compared to other cancer types, patients with HNC have the highest prevalence of psychological distress, with a associations found between nutritional status, dietary intake and psychological status [ 85 , 86 ]. However, additional factors also contribute to psychological distress in this population, in particular anxiety in one-third of the population, and depression, experienced by 15–50% of patients [ 87 ].…”
Section: Consequences Of Malnutritionmentioning
confidence: 99%